Preservation of blessings and their disappearance in The Holy Quran - Lakhnig, Larbi Mohamed (Journal of Islamic Sciences, 2023)
As long as the blessings are not on the same scale, and their acquisition and disappearance are governed by divine laws. And since the concrete fact of this can only be fully understood through revelation, therefore the proper conception and extraction and formulation of the divine laws related to this subject, requires extrapolating the uses of the term studied and of its derivatives in the Holy Quran and to study them according to a solid scientific approach. To achieve this objective, I will adopt a descriptive method based on the study of terminology. Among the results of this study is that blessings are governed by divine laws and that their types are multiple and they differ according to the time of their obtaining, and according to their renewal and their continuity, as well as in consideration of the ways by which they reach the servants.